Effects of loneliness, need for cognition and life satisfaction on involvement in the twilight saga : segmentation and product preferences of the Twilight Saga’s consumers. - Chen, Joan Shumin. (2010)
This report aims to find out how loneliness, need for cognition and life satisfaction affect individuals’ involvement in the Twilight Saga. These three factors are psychosocial variables pertaining to escapism. Our results partially supported the hypotheses that respondents who experience loneliness and have a low need for cognition are more likely to be involved in the Twilight Saga. However, no significant results proved the link between low life satisfaction and involvement. We also took into account significant interacting effect between loneliness and life satisfaction in our model.